Kajian Yuridis Terhadap Mantan Suami yang Tidak Memenuhi Kewajiban Nafkah Anak Perspektif Hukum Pidana - Ickbal Hofifi Bairuroh; Triana Apriyanita; Sifa Mulya Nurani; Septiayu Restu Wulandari; Trias Saputra (JURNAL HUKUM PELITA, 2025)
This study discusses the obligation to provide child support by ex-husbands after divorce, which is reviewed from a criminal law perspective. The obligation to provide child support is part of the protection of children's rights as regulated in laws and regulations in Indonesia, Law Number 1 of 1974 concerning Marriage, Law Number 35 of 2014 concerning Child Protection, and The Criminal Code (KUHP). Problems arise when ex-husbands do not carry out these obligations, which has the potential to cause legal consequences. This study aims to examine the legal form of criminal responsibility for ex-husbands who are negligent or intentionally do not provide support to their children. The method used in this study is the normative legal method with a statutory approach and case studies. The results of the study indicate that the non-compliance of ex-husbands in fulfilling their child support obligations can be categorized as a form of child neglect which has criminal implications. Law enforcement in this case still faces various obstacles, both from normative and implementative aspects. Therefore, it is necessary to strengthen regulations and increase legal awareness for the community to ensure the fulfillment of children's rights after divorce